Pengembangan Aplikasi Latihan Fisik untuk Menjaga Kebugaran Tubuh di Masa Pandemi berbasis Android - Ismail Risky Rahmansyah; Ratih Kartika Dewi; Fais Al Huda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The COVID-19 pandemic (Coronavirus Disease 2019) has changed most people's habits, people are encouraged to pay attention to health and obey health protocols, one way is by doing sports, but according to (Furkan, 2021) not all types of exercise can increase immunity, The right exercise will increase immunity, but on the other hand, exercise that does not pay attention to FITT (Frequency, Intensity, Type and Time) will actually weaken immunity. This prompted the author to develop physical exercise applications to maintain physical fitness during the pandemic. Application development is carried out using the SDLC waterfall with needs that have been defined at the beginning through interviews and literature studies. The stages of system development include requirements analysis which consists of an overview of the system, numbering rules, identification of actors, functional requirements and non-functional requirements. The design and implementation consists of designing activity diagrams, sequence diagrams, class diagrams, database design and implementation, program code, and interfaces. The results of the implementation were then tested using the black box method. The results of this black box test obtained a final value of 100% valid from all functionality. Other tests carried out are compatibility where test results are generated that the application can run on the Android platform version 5.1 and above and Usability testing produces a value of 70.5 with the Acceptable category.